Prescrições de uma "ciência positiva da moral" para a solução de um dilema ético: elementos para a leitura Da divisão do trabalho social - Sergio Luis Pinto Coelho (2007)
The Division of Labour in Society inaugurates Durkheims Sociology. Understanding his book implies knowing the origins and goals of the subject, as Durkheim himself meant it. This study is aimed at investigating the scientific principles behind his book, based on the French historical background as experienced by Durkheim and the influences from French and German scientific traditions, providing different and complementary meanings to his thesis without which its understanding would be affected. Thus, The Division of Labour in Society will be shown to be an attempt by Durkheim to solve a moral dilemma in regard to the individuals participation in the societys economic sphere through professional groups, as he observed in the introduction to his book.